A Synergistic Approach to Improving Reading Comprehension: Integrating the Listen-Read-Discuss Strategy into Flipped Learning - Istiqamah, Nurul; Idham, Afif Zuhdy; Rauf, Wahyuddin (JOINT: Journal of Inspirational English Language Teaching, 2025)
This study investigated the impact of integrating the flipped learning model with the Listen–Read–Discuss (LRD) strategy on students’ reading comprehension at MA Muhammadiyah Padaelo. The research employed a pre-experimental one-group pretest–posttest design to examine changes in students’ reading comprehension following the implementation of the combined instructional approach. In the flipped learning setting, students explored lesson materials outside the classroom, while in-class sessions were devoted to interactive LRD activities that promoted deeper engagement with the texts. The findings revealed a significant improvement in students’ reading comprehension after the intervention, with the mean score increasing from 55 in pre-test to 85 in post-test. These results indicate that the integration of flipped learning and the LRD strategy can effectively enhance students’ reading comprehension by fostering active participation, critical thinking, and meaningful interaction with reading materials.